Engineering student attitudes to e-reading in remote teaching environments - Welsen, Sherif; Pike, Matthew; Walker, James (2020)
Rational: Academic libraries are increasingly offering online e-books because they provide convenient access for students, cost savings, logistical advantages and significant portability. Current research suggests that this trend will continue in the future. In parallel with the growth of the e-book market and the development of e-book library collections, librarians and information scientists have conducted a number of research studies to investigate the impact of e-books on collection development: specifically, relating to the challenges and questions of e-book management and service. Consequently, researchers have considered it pertinent to explore the behaviours and strategies of e-book readers. Scope: In January 2020, institutions around the globe faced significant disruption due to COVID-19. Many universities accelerated their adoption of online/e-learning approaches in response to the COVID-19 epidemic. Though e-books were at an early stage of adoption and the culture of using them in academia was slowly growing, they suddenly became the preferred option, if not the sole option because libraries were closed. Accordingly, some of the popular publishers; for example, Cambridge University Press, have offered online higher education textbooks as free-to-access. Over 700 textbooks were available for more than 2 months, regardless of whether those textbooks had previously been purchased. Furthermore, MIT Press offered complimentary access to its catalogue of e-books to support faculty and students who were working and learning remotely. Methodology: Despite increasing interest from librarians and learning technologists, prior to 2020, there were few well conducted studies investigating the habits of e-book users, especially amongst engineering students. Notwithstanding the challenges arising from the COVID-19 pandemic, an opportunity has arisen to survey student attitudes regarding the adoption of e-reading in an academic context. In this paper, a case study is presented that investigates the impact of the mandatory use of an e-book textbook in a final year undergraduate engineering module at the University of Nottingham Ningbo China. The paper investigates Science and Engineering students’ usage and attitudes towards e-books when using their available e-readers, which include PCs or portable devices. A cross-sectional survey containing 5 nominal questions, 2 open questions and 17 Likert questions was developed and deployed to final year students from two programmes: Electrical and Electronic Engineering and Mechatronics Engineering. These students were attending the module titled Integrated Circuits and Systems. Findings: The results of this study highlight approaches for improving support for e-reading in an academic environment. Of particular interest to librarians are student attitudes after their adjustment to e-books, which have implications for future purchasing decisions. Furthermore, student strategies for adjusting their learning techniques as a result of forced engagement with e-books illustrate preferences that can inform educators. In conclusion, the forced adoption of e-books has presented the opportunity to investigate student acceptance and strategies. This research provides evidence for purchasing decisions and strategies for adopting e-books in wider Higher Education syllabi.